2014
DOI: 10.3892/mmr.2014.2536
|View full text |Cite
|
Sign up to set email alerts
|

Association study of miR-149 rs2292832 and miR-608 rs4919510 and the risk of hepatocellular carcinoma in a large-scale population

Abstract: Polymorphisms in pre‑microRNAs (miRNAs) or mature miRNAs may influence miRNA processing or target binding, thus contributing to tumorigenesis and cancer development. The present study aimed to evaluate whether miR‑149 rs2292832 (C>T) and miR‑608 rs4919510 (G>C) are associated with the risk and clinical characteristics of hepatocellular carcinoma (HCC) in a large‑scale population. miR‑149 rs2292832 and miR‑608 rs4919510 were genotyped in a total of 993 patients with HCC and 992 unrelated healthy subjects by Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…After further identification and screening individual study, 43 articles (49 studies) [1153] underwent full-text assessment, and 6 articles (10 studies, not including one site according to HWE) [14, 17, 19, 20, 35, 42] were excluded due to inconsistently with HWE. Finally, 37 articles (40 studies) [1113, 15, 16, 18, 21–34, 3641, 4353] were conducted in quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After further identification and screening individual study, 43 articles (49 studies) [1153] underwent full-text assessment, and 6 articles (10 studies, not including one site according to HWE) [14, 17, 19, 20, 35, 42] were excluded due to inconsistently with HWE. Finally, 37 articles (40 studies) [1113, 15, 16, 18, 21–34, 3641, 4353] were conducted in quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 39 eligible studies met the prespecified inclusion criteria, in which two articles [24, 52] included two tumor types respectively, and one article included [23] rs2292832 and rs895819. As for rs2292832, involving 9,994 cases and 10,757 controls were ultimately analyzed from 21 studies (20 articles) [1113, 15, 16, 18, 21–34], and 19 studies (17 articles) [23, 3641, 4353] involving 7,800 cases and 9,060 controls for rs895819.…”
Section: Resultsmentioning
confidence: 99%
“…performed a meta‐analysis and found that miR‐196a2 rs11614913 was associated with susceptibility to HBV infection, whereas no evidence of association was found between miR‐146a rs2910164, miR‐499 rs3746444, and miR‐149 rs2292832 with hepatitis B risk. However, a different study found that miR‐149 rs2292832 was associated with HBV‐related HCC . In addition, Su et al., (2015) recently identified an association between miR‐146a rs2910164 and the development of HCC in an Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have revealed that lncRNAs have important influence in tumorigenesis, metastasis, and prognosis and drug resistance of gastric cancer [1]. While the functional role and molecular mechanism of many GCassociated lncRNAs remain undetermined, recent studies revealed that several lncRNAs are associated with GC progression, such as H19, FENDRR, and MRUL [14][15][16].…”
Section: Discussionmentioning
confidence: 99%